The clinical, laboratory, and microbiological profile of patients with sepsis at the Internal Medicine Inpatient Unit of Dr. Cipto Mangunkusumo National General Hospital, Jakarta (Faculty of Medicine Universitas Indonesia, 2004)
At the moment, the diagnosis of sepesis is established based on the criteria of the presence of a clinical manifestation of systemic inflammatory response syndrome/SIRS, infection, and organ dysfunction. In the last two years, the idea to add several additional parameters to these criteria has developed, with the proposition to use the acronym PIRO (P: predisposition, I: infection, R: response, and O: organ failure). Clinical manifestations of sepsis at each hospital or treatment unit may differ according to the severity of sepsis, the focus of infection, comorbidity, and organ dysfunction or failure. This study evaluated the demographic, comorbidity, source of infection, SIRS manifestation, organ dysfunction, and microbiological profile of sepsis at the Internal Medicine Inpatient Ward of Dr. Cipto Mangunkusumo National General Hospital, Jakarta. A correlative, cross-sectional, descriptive study was performed on 42 subjects with sepsis, severe sepsis, and septic shock. The study was performed at the Inpatient Ward of Dr. Cipto Mangunkusumo NAtional General Hospital, Jakarta, in the year 2002. Clinical and laboratory (hematological, biochemical, and blood gas analysis) data, as well as results of aerobic cultures of the blood and other specimens were recorded. The criteria of sepsis used were based on that of the American College of Chest Physician and the Society of Critical Care Medicine in 1992. The results of the study demonstrated a proportional distribution of sepsis based on age and sex, with comorbidity in 88% of subjects, consisting of diabetes mellitus and other chronic diseases. The most common sources of infection were the lungs, skin-soft tissue, abdomen, and urinary tract, with Gram-negative bacteria more commonly found than Gram-positive bacteria. SIRS manifestation was found among over 70% of subjects, with the most common manifestations being tachycardia and tachypnea. The most common manifestations of organ dysfunction were reduced consciousness, metabolic acidosis, renal dysfunction, and a lower mean arterial pressure. There was a correlation between these parameters and the degree of sepsis. (Med J Indones 2004; 13:90-5)Keywords: sepsis, clinical manifestation, microbiology